BARRIERS TO EARLY DETECTION OF HIV/AIDS IN PREGNANT WOMEN IN MEDAN HELVETIA SUB-DISTRICT MEDAN CITY 2023 - Martalena Br S Kembaren; Ida Yustina; Nurmaini Nurmaini; R Kintoko Rochadi; Fikarwin Zuska; Fazidah Fazidah (International Journal of Midwifery Research, 2023)
Pregnant women are one of the populations at risk of contracting Human immunodeficiency Virus (HIV), Syphilis, and Hepatitis B diseases in children more than 90% are infected from their mothers. The risk of mother-to-child transmission for HIV/AIDS is 20%-45%, for Syphilis is 69-80%, and for Hepatitis B is more than 90%. All three have the same transmission routes in the form of sexual intercourse, blood, and this transmission mostly occurs through vertical transmission from mother to fetus during pregnancy. Triple elimination is a program that aims to achieve and sustain mother-to-infant elimination of HIV/AIDS, Hepatitis B, and Syphilis in order to achieve better health for women, children, and their families through a coordinated approach. Detection and prevention of HIV incidence during pregnancy or postpartum should be prioritized and is essential to reduce mother-to-child transmission of HIV. In line with the increasing cases of mother-to-child HIV transmission, the government has made various control efforts through the PPIA or PMTCT (Prevention of Mother-to-Child Transmission) program. This research used field research to obtain qualitative data. Researchers go to the field to make observations about a phenomenon in a natural situation and are closely related to participant-observation. The results of the research obtained ANC services have been running well. Barriers to ANC access are related to cultural aspects and organizational systems that have not made maximum efforts to improve services, especially STIs (HIV/AIDS). At Puskesmas Helvetia, every pregnant woman will be directed to do HIV testing. Integrated ANC services have been running well. Routine technical training to improve obstetric competence for midwives and other supporting training needed as well as laboratory examination training for laboratory analysts (including STI and HIV/AIDS testing training) has been running well and systematically.